2022
DOI: 10.3390/fermentation8120676
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fermentation on the Physicochemical Properties and Aroma of Lamb Liver Paste

Abstract: The probiotic fermentation of lamb liver paste is a new method with which to utilize sheep by-products and address the issue of waste. In this study, a pH meter, chromaticity meter, texture analyzer, and gas chromatograph–mass spectrometer (GC–MS) were used to determine various indicators. The objective was to investigate the effect of fermentation on the physical properties and aroma of lamb liver paste. The results showed that the L* (brightness), a* (redness), and b* (yellowness) of the samples were signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The edition featured ten publications (nine original research papers and one review) covering diverse topics. Special mention should be given to papers focusing on the aroma profiles of non-traditional foodstuffs [1][2][3].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The edition featured ten publications (nine original research papers and one review) covering diverse topics. Special mention should be given to papers focusing on the aroma profiles of non-traditional foodstuffs [1][2][3].…”
mentioning
confidence: 99%
“…Liu et al [2] reported on the aroma compounds that are produced during the fermentation of lamb liver paste. Hung et al [1] showed what effect the addition of starter cultures like Bacillus subtilis and S. cerevisiae can have on the analytical and sensory composition of seaweed.…”
mentioning
confidence: 99%